K. H. Ahmad Dahlan: Konsep dan Implementasi “Kemanusiaan” (1912-1936) - Wasno Wasno; Rhoma Dwi Aria Yuliantri (Jurnal Sejarah Citra Lekha, 2022)
Ahmad Dahlan is an Islamic reformer known for one of his concepts of humanity (compassion). This research aims to examine Ahmad Dahlan's thoughts and practices about the humanitarian concept of "compassion" based on love to unite people who are part of the basic values of the prophetic spirit. This research employed the historical method utilizing sources from the results of previous studies, Verslag Openbare Vergedering PKO (No. 10), and a collection of photo archives from the K.H. Ahmad Dahlan Foundation. The research results show that Ahmad Dahlan applied the concept of "compassion" in community life rather than memorizing the concept in developing the idea of humanity based on the Al-Quran (surah Al-Ma'un). Ahmad Dahlan's ideas began to be applied by his pupils by doing charity to the beggars. A more real realization of that idea was the establishment of General Suffering Helpers (later to become PKO Muhammadiyah Hospital), orphanages, and others.